Molecular Detection of Leprosy: A Literature Review - Hersa Firda Kartika; Tutty Ariani (International Journal of Science and Society, 2026)
Leprosy is an infectious disease caused by the bacterium Mycobacterium leprae, which can lead to permanent damage to the skin, nerves, and tissues. Early diagnosis is crucial to prevent further complications. Molecular technology has emerged as a significant tool in enhancing the accuracy and speed of leprosy diagnosis. By employing techniques such as Polymerase Chain Reaction (PCR) and genetic analysis, bacterial DNA detection can be performed even at the early stages of infection, when clinical symptoms are not yet apparent. Additionally, this technology allows for the identification of different bacterial strains, providing insights into the epidemiology and transmission patterns of the disease. The application of molecular technology also has the potential to improve the monitoring of treatment effectiveness and resistance of therapy regiments. Although challenges remain in accessibility and implementation of this technology in countries with high prevalence, innovations in molecular diagnosis offer new hope for the control and eradication of leprosy globally. Further research and investment in healthcare infrastructure are essential to maximize the potential of this technology in the diagnosis and management of leprosy.